2017
DOI: 10.5812/ircmj.14591
|View full text |Cite
|
Sign up to set email alerts
|

Anthropometric Indices in the Prediction of Hypertension in Female Adolescents

Abstract: Background: Identifying the best marker for appropriate screening of risk factors of chronic diseases seems necessary in any society. Objectives: This study aimed at performing a comparative evaluation of anthropometric indices to determine a better marker for prediction of high blood pressure in adolescents. Methods: This cross-sectional study was done during 2013 on 1046 students, aged 11 to 19 year old in Kashan, who were chosen by cluster and class sampling method. Height, waist circumference (WC), waist-t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
4
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 39 publications
3
4
1
Order By: Relevance
“…The current study found that the optimal cut-off points of BMI, WC and WHtR for the prediction of high BP were lower than the threshold to define obesity in adolescents, replicating the results of previous studies 37 49. In the present study, the optimal WHtR cut-off values were 0.46 in men and 0.45 in women, which were close to the WHtR cut-off values (<0.5) reported by previous studies for the prediction of hypertension37 as well as metabolic syndrome50 and CVD risk among adolescents 51.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…The current study found that the optimal cut-off points of BMI, WC and WHtR for the prediction of high BP were lower than the threshold to define obesity in adolescents, replicating the results of previous studies 37 49. In the present study, the optimal WHtR cut-off values were 0.46 in men and 0.45 in women, which were close to the WHtR cut-off values (<0.5) reported by previous studies for the prediction of hypertension37 as well as metabolic syndrome50 and CVD risk among adolescents 51.…”
Section: Discussionsupporting
confidence: 90%
“…The current study found that the optimal cut-off points of BMI, WC and WHtR for the prediction of high BP were lower than the threshold to define obesity in adolescents, replicating the results of previous studies 37 49. In the present study, the optimal WHtR cut-off values were 0.46 in men and 0.45 in women, which were close to the WHtR cut-off values (<0.5) reported by previous studies for the prediction of hypertension37 as well as metabolic syndrome50 and CVD risk among adolescents 51. Although a WHtR of ≥0.5 was previously proposed as the universal cut-off value to assess abdominal obesity and cardiometabolic risk,14 the cut-off of 0.5 resulted in poor sensitivity in predicting CVD risk among adolescents and may not be efficiently used across different ethnic groups 52.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Regarding the cutoff point for WHtR (>0.41) identified in this study for HBP screening in males, another study presented the same cutoff point of 0.41 ( 68 ). The cutoff point of 0.41 for WHtR is below cutoff points in other studies ( 21 , 23 , 63 , 65 , 66 , 69 71 ). Since 1995 ( 72 ), the year of the creation of anthropometric indicator WHtR, a universal cutoff point (0.50) has been established to identify overweight individuals from those with normal weight and to be considered a risk factor for cardiovascular diseases, among them, hypertension, which can be used for both sexes and different age and ethnic groups ( 72 , 73 ).…”
Section: Discussioncontrasting
confidence: 67%
“…22 However, WHtR has been recommended as a simple screening tool and a more convenient indicator for assessing central adiposity, which could be superior to BMI and WC for the evaluation of cardiometabolic risk in both men and women. 23 In the present study, the prevalence rates of abdominal obesity based on WC and WHtR were 20.9% and 59.4%, respectively. These rates were higher in females when compared to males (35.2% and 18.2% vs. 81.5% and 55.4%, respectively).…”
Section: Discussionsupporting
confidence: 42%